INTEGRATING PEER TUTORING VIDEO WITH FLIPPED CLASSROOM IN ONLINE STATISTICS COURSE TO IMPROVE LEARNING OUTCOMES - Ramadoni Ramadoni; Kao Tai Chien (Jurnal Infinity, 2023)
Online learning has become a solution in the field of education lately. Statistics is one of the subjects students must take at the university level. Learning statistics takes work for students. Based on the author's investigation, there are three obstacles to students in online learning: the constraints of students in understanding the material, the online learning process, and the assignment process. The sample in this study is a student with an Indonesian worker background in Taiwan, where they study online at night. Since an appropriate online learning method is needed to achieve student success, this study analyzes three online learning methods: conventional online learning, conventional flipping classes in online learning, and innovative flipped classrooms in online learning. This study investigates the three learning methods' results in differences in gender, job, and age. The results obtained indicate that there are significant differences in student learning outcomes in the three sample groups. Further analysis showed that the innovation of flipped classrooms in online learning significantly differs from the other two learning methods. Based on the type of job, there are differences in student learning outcomes taught in the conventional flipped classroom in online learning. It was also seen in the analysis of combining all student learning outcomes taught with online learning that there were differences in student learning outcomes regarding the job. A household assistant is better than a factory worker because students who work as household assistants have more flexible time to watch videos and repeat them than those who work as factory workers.